Wand Stretching Exercise Decreases Abdominal Obesity Among Adults With High Body Mass Index Without Altering Fat Oxidation - Puengsuwan, Punnee; Kuo, Chia-Hua; Chaunchaiyakul, Rungchai; Nanagara, Ratanavadee; Leelayuwat, Naruemon (Frontiers in Physiology, 2020)
Rationale We designed a wand-based muscle stretching (WE) exercise program, which has become increasingly popular in physical therapy and has been used for elderly patients with adhesive capsulitis. However, studies regarding the effects of WE training on abdominal obesity and measures of cardiovascular risk factors among overweight/obese adults aged ≥55 years are rare. Purpose The objective of this study is to evaluate the effects of a 15-week wand stretching exercise program on waist circumference and cardiovascular risk factors in sedentary adults aged 55–70 years. Methods A total of 124 participants were randomly assigned to either participate in wand stretching exercise (WE) over a 15-week period or a control group (n = 62 each). Sixty participants in the WE group (26 overweight and 34 obese) and 51 in the control group (29 overweight and 22 obese) completed the study. The WE program included wand-assisted muscle stretching exercise on both the upper body and lower body for 40 min per day, 5 days per week, whereas the control group maintained their sedentary lifestyle. Results No significant improvements were observed in plasma glucose, insulin, and the homeostatic model assessment of insulin resistance (HOMA-IR) after exercise training. Compared with the control group, the WE group had more significant reductions in waist circumference among participants with a body mass index (BMI) < 25 kg/m2 (−2.6 cm, 95% CI: −4.19 to −0.97 cm, d = 0.48) and BMI > 25 kg/m2 (−2.5 cm, 95% CI: −4.1 to −0.9 cm, d = 0.59) (both P < 0.01). Furthermore, within groups, a significant increase in % fat free mass was observed after WE training. The basal metabolic rate was slightly increased, but the fat oxidation rate remained unaltered in the WE group. Improvements in low-density lipoprotein cholesterol to high-density lipoprotein cholesterol were minimal after WE. Significant reductions in high-sensitivity C-reactive protein were observed after WE only for participants with a BMI <25 kg/m2. Conclusion The results suggest redistribution of a carbon source from the abdominal region to challenged skeletal muscle, following prolonged WE training. This abdominal fat reducing outcome of the WE is unlikely to be associated with fatty acid oxidation.